AB0647 Arthritis in systemic lupus erythematosus: A patient's perspective. (23rd January 2014) - Tani, C.; Carli, L.; Carbone, M.; della Rossa, A.; Bombardieri, S.; Mosca, M.
Abstract : Background: Joint involvement in systemic lupus erythematosus (SLE) is common and occurs in over 80% of patients. Even if traditionally considered mild and non erosive, joint involvement may cause chronic pain, joint stiffness and deformities and, eventually, loss of joint function. Objectives: To evaluate patient general health, pain, fatigue, physical functioning, quality of life and perception of disease activity in SLE patients and to explore in what extent and in what respect joint involvement contributes to these outcomes. Methods: Outpatients with SLE referring to our unit were consecutively enrolled. At study entry, physical examination, including a complete joint count (44 joints), was performed and disease activity and damage were assessed. The following questionnaires were administered: HAQ, SF-36, FACIT; in addition, patients were asked to complete VAS (0-100mm) scales evaluating patients reported pain, global disease activity and general health (GH, were 0 is best, 100 is worst). Age and sex matched outpatients with a diagnosis of rheumatoid arthritis (RA) were enrolled as controls. Results: 30 female patients were enrolled (mean age 39.5±9, min 22- max 63) with a mean disease duration of 14±7 years (min 1- max 29); the mean disease activity as expressed by the ECLAM score resulted 1.6±1 (min o- max 3) and mean SLICC-DI score was 0.5±0.9 (min 0- max 3). At enrollment articular symptoms were present in 17 patients (57%): arthritis in 6 patients (20%) with a mean swollen and tender joints count of 2, 7±6 (min 0-max 19) and 6±6 (min 0-16) respectively; Jaccoud's arthropathy in 2 (7%) patients; significant morning stiffness lasting for more minutes in 9 (30%). The mean HAQ score resulted 0.28 (±0.7; min 0- max 3.2) with 7 (22%) patients reporting at least some difficulties (HAQ>0) in daily life activities. The mean VAS score for pain resulted 25mm (±27, min0 max 100), patient reported disease activity resulted 21mm (±5, min 0, max 90), mean GH values were 28 mm(±25, min 0- max 85); mean FACIT score resulted 1, 3 (±0, 3, min 0, 4- max 1, 6). The presence of articular symptoms significantly correlates with pain perception (p=0.004), with poorer quality of life (as expressed by HAQ, p=0.016), GH (p=0.04) and patients perception of disease activity (p=0.01). On the contrary, systemic disease activity as expressed by the ECLAM score resulted significantly associated with poorer quality of life (p=0.05) but not with pain, fatigue, GH nor patient's perception of disease activity. Disease damage and, in particular, Jaccoud's arthropathy, seem to significantly interfere with quality of life and GH. No significant differences were observed in these patients reported outcome between RA and SLE with arthritis. Conclusions: In this cohort of patients with long disease duration but low systemic disease activity, the presence of active joint involvement significantly affects the quality of life by conditioning chronic pain and a negative awareness of the general health similarly to what observed in RA. In addition, arthritis impacts significantly on patient's perception of disease activity. These data highlight the patient's perspective on joint involvement in SLE and emphasize the need for joint symptoms control during the active phases and a proactive treatment strategy to prevent joint damage. Disclosure of Interest: None Declared